On-board hydrogen-rich syngas production via waste heat recovery from compression-ignition engines: maximizing hydrogen content with novel multi-objective algorithms - Agbulut, Umit; Vozka, Petr; Bakir, Huseyin; Brieu, Nathan A.; Polat, Fikret; Saridemir, Suat (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
A significant portion of fuel energy in internal combustion engines is lost as waste heat, yet limited efforts have been made to recover it effectively. This research explores the utilization of exhaust heat from a diesel engine to produce H2-rich syngas through the methanol-steam reforming (MSR) process. The engine operates at varying loads (15, 30, 45, and 60 Nm) while maintaining a constant speed of 2000 rpm. Exhaust heat is redirected to an MSR reactor, where the methanol-to-water (MtW) molar ratio is adjusted (0.5, 1, 1.5, and 2). Results reveal that the highest hydrogen content in syngas (70.3 %) is achieved at an engine load of 30 Nm and an MtW ratio of 1. To further optimize hydrogen production, three novel algorithms (DSC-MOPSO, MOSPO, and MOGWO) are applied to key operation parameters. Optimization increases hydrogen content to 72.5 % with DSC-MOPSO, 72.4
Keywords: Hydrogen-rich gas; Methanol-steam reforming; Waste heat recovery; Optimization algorithms; METHANOL; REACTOR; Chemistry; Electrochemistry; Energy & Fuels